Implementasi Program 3M (Masyarakat Melek Metrologi) dalam Rangka Pemasaran Sosial di Kota Bandung oleh Direktorat Metrologi - Raisa Rafifiti Choerunnisa; Wilda Widya Harahap (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
This research is motivated by the fact that many people do not know what Legal Metrology is and people do not care enough to know about this, so social marketing is needed to be able to change people's behavior and spread positive information about Legal Metrology, namely the social marketing program 3M (Metrology Literacy Society). This research aims to determine the implementation of the 3M social marketing program by the Metrology Directorate and disseminate information about Legal Metrology which was analyzed using Kotler and Lee's Social Marketing Theory which includes Social Issues, Behavioral Goals and Targets, Barriers and Benefits of the Marketing Mix and Supervision and Evaluation. This research uses qualitative methods by collecting data through interviews, observation and literature study. The results of this research show that the implementation of social marketing is not yet optimal because based on social marketing theory there are 3 dimensions that are not optimal, namely community targets that are not yet structured and prioritized, monitoring and evaluation (monev) is not carried out and the dissemination of information is not yet comprehensive through social media. So researchers recommend adding an online media platform, namely the Tiktok application, creating an encyclopedia with the name "Metropedia" and creating priority target communities that are directly related to Legal Metrology. Keywords: Social Marketing, Legal Metrology, Dissemination of Information